Optical and Thermal Properties of Acid Red Doped Triglycine Acetate Crystal for Optoelectronic Applications. Issue 2 (2nd November 2021) - Chaithra, G.; Deepthi, P. R.; Challa, Malathi; Sukhdev, Anu; Kumar, P. Mohan; Shanthi, J.
Abstract: A positive change in crystal can be induced by dye. Pure and Acid Red 1 dye (AR) doped triglycine acetate (TGAc) single crystals are synthesized by solution approach to enrich the characteristics of pure TGAc crystals. The crystalline nature of the grown crystals is investigated using powder X‐ray diffraction. The Scherrer method has been used to calculate the crystallite size of both developed crystals and is compared to the Williamson and Hall method. Fourier transform infrared spectroscopy confirms the existence of several functional groups as well as dye inclusion in the produced crystals. Four distinct absorption bands are found in UV–vis–NIR absorption spectra at the location where AR dye is inserted into the TGAc matrix. Different optical constants, such as optical bandgap ( E g ), extinction coefficient ( k ), refractive index ( n ) and optical conductivity ( σ ) are measured for both samples based on transmittance measurements. The thermal stability and decomposition temperature of 0.05 mol% AR dye doped TGAc are found to be higher. The doped crystals' improved optical characteristics and thermal stability prove their applicability for optoelectronic applications. Abstract : Pure and Acid Red 1 dye (AR) doped triglycine acetate (TGAc) single crystals are grown by solution method. Four distinct absorption bands are observed in the UV‐Vis‐NIR absorption spectra at the location where AR dye is inserted into the TGAc matrix. The thermal analysis shows that the decomposing point of the dye doped TGAc crystals increases with the dopant concentration which indicates the high quality of the crystal.